EKSISTENSI LEMBAGA KEUANGAN MIKRO: CIKAL BAKAL LAHIRNYA BMT DI INDONESIA - SLAMET MUJIONO (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The theme of the article is the banks and financial institutions. The purpose of this paper is to analyze the existence of BMT in Indonesia. Microfinance Institutions have a long history. The emergence of Sharia Micro Finance Institutions is a reaction to the existence of conventional financial institutions. BPRS that is the first Sharia Micro Financial Institution. The BPRS emerges as a microfinance institution in the form of a Savings and Loans Cooperative. Then made a pilot project with the name Baitul Maal wat Tamwil (BMT). Society is very enthusiastic about the presence of BMT. The Indonesian government makes rules that regulate, build and supervise BMTs.